Calcium sensing receptor regulate claudin-14 via PKA-STAT3 pathway in rat model of nephrolithiasis - Luo, Peiyue; Chen, Tao; Zheng, Liying; Zou, Junrong; Zou, Jun; Li, Wei; Chen, Qi; Cheng, Le; Qian, Biao (Frontiers in Pharmacology, 2024)
Background The calcium-sensitive receptor (CaSR) has been identified as a key factor in the formation of kidney stones. A substantial body of research has illuminated the function of CaSR in stone formation with respect to oxidative stress, epithelial injury, crystal adhesion, and stone-associated proteins. Nevertheless, as a pivotal molecule in renal calcium excretion, its pathway that contributes to stone formation by regulating calcium supersaturation remains underexplored. Methods An in vitro rat calcium oxalate kidney stone model was established through the co-cultivation of calcium oxalate monohydrate (COM) with NRK-52E cells, while an in vivo model was constructed using the ethylene glycol method. Subsequently, the level of the CaSR-claudin-14 pathway was determined. To further elucidate the molecular pathway of CaSR-mediated regulation of claudin-14, drugs were selectively added to the in vitro and ex vivo kidney stone models, and the expression of claudin-14 and the levels of stone formation were detected. Moreover, the direct regulation of claudin-14 by CaSR with STAT3 serving as a transcription factor was examined via the dual luciferase assay. Eventually, a Cldn-14 knockout rat model and a model of kidney stone induction by ethylene glycol were generated using CRISPR-Cas9 technology to further clarify the role of claudin-14 in the CaSR-regulated formation of kidney stones. Results In vitro and in vivo observations revealed that calcium oxalate induces high expression of CaSR-claudin-14. Specifically, CaSR regulates claudin-14 expression through phosphorylation modification of STAT3 via protein kinase A (PKA). In vitro, the intervention of PKA and STAT3 reversed the elevated claudin-14 levels and stone formation induced by CaSR. Finally, we generated cldn-14 knockout rats using CRISPR-Cas9 technology and observed that ethylene glycol still induced stone formation in these animals. Nevertheless, the specific activation or inhibition of CaSR demonstrated no notable impact on stone formation. Conclusion The results of our study indicate that calcium oxalate crystals induce the activation of the pro-stone pathway of CaSR. That is, activated CaSR regulates claudin-14 levels via the PKA-STAT3 pathway, which further promotes calcium salt stone formation. The role of CaSR in the regulation of stone homeostasis is further enriched.